Gradient delivery of bioactive molecules across porous hydrogels - Eltaher, Hoda M.M.A. (2016)
Tissue regeneration approaches involve the recreation of biochemical and mechanical cues dictating tissue fate. Gradients of chemical cues are common in the natural microenvironment and are usually accompanied with gradual changes in cellular responses. Consequently, thorough understanding of biomolecule gradient development, their effective concentrations and the corresponding cellular responses as a function of time and space are essential for efficient design of scaffolds for biomedical applications. Here, we developed a compartmental diffusion model to study the development and measurement of biomolecule gradients. The model was validated to ensure effective spatiotemporal measurements of diffusing species within three-dimensional (3D) hydrogels. Results confirmed that the factors regulating the diffusing molecules’ behaviour in hydrogel matrices were dependant on the size of the diffusing species and the interaction with the matrix. The source compartment was subsequently replaced by polymeric particulate depots with tuneable characteristics to maintain structural protein stability and provide controlled temporal release of proteins and the diffusion through the hydrogel compartment was accordingly monitored. Glycosaminoglycan enhanced transduction (GET) technology was employed to study 3D gradient transduction of reporter protein in cell-laden hydrogels and to examine the effect of cells on the diffusion of biomolecules. Results demonstrated that cellular uptake of GET proteins altered the diffusion pattern as compared to acellular scaffolds and cells themselves acted as a sink that maintained steep GET protein gradients over the 5 mm wide scaffold. Furthermore, the synergistic combination of poly-arginine cell penetrating peptide (CPP) together with the cell membrane binding peptide using the GET technology demonstrated significant intracellular transduction in a gradient fashion in comparison to CPP alone. Employing GET technology and the compartmental diffusion model in the gradient delivery of the transcription factor MyoD to cell-laden hydrogels, resulted in directing the cells towards myogenic differentiation. However, the gradient pattern of differentiation was not clearly observed due to the limited number of genes examined. In conclusion, the model can be employed for the effective spatiotemporal gradient delivery of functional proteins to achieve the tissue complexity observed in the native tissues.